2002
DOI: 10.1128/aem.68.9.4307-4314.2002
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Lysogeny as Depicted by Prophage Induction in Tampa Bay, Florida

Abstract: A seasonal study of the distribution of lysogenic bacteria in Tampa Bay, Florida, was conducted over a 13-month period. Biweekly water samples were collected and either were left unaltered or had the viral population reduced by filtration (pore size, 0.2 m) and resuspension in filtered (pore size, 0.2 m) water. Virus-reduced and unaltered samples were then treated by adding mitomycin C (0.5 g ml ؊1 ) to induce prophage or were left untreated. In order to test the hypothesis that prophage induction was phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
194
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(225 citation statements)
references
References 30 publications
(25 reference statements)
26
194
1
4
Order By: Relevance
“…The sudden collapse in the D. circinale population strongly implicates an external biological effector, such as viral lysis or bacterial predation, neither of which was addressed at length within the scope this study. In this regard, numerous studies have demonstrated biotic mechanisms for the rapid dispersal of cyanobacteria from surface waters that may explain this observation, including phage-induced lysis (Proctor and Fuhrman, 1990;Williamson et al, 2002;Matteson et al, 2011;Steffen et al, 2015), bacteria-induced lysis (Rashidan and Bird, 2001), grazing by protists (Ger et al, 2014), algicidal compounds (Luo et al, 2013; and cyanobacterial programmed cell death (Franklin, 2014).…”
Section: Abioticmentioning
confidence: 99%
“…The sudden collapse in the D. circinale population strongly implicates an external biological effector, such as viral lysis or bacterial predation, neither of which was addressed at length within the scope this study. In this regard, numerous studies have demonstrated biotic mechanisms for the rapid dispersal of cyanobacteria from surface waters that may explain this observation, including phage-induced lysis (Proctor and Fuhrman, 1990;Williamson et al, 2002;Matteson et al, 2011;Steffen et al, 2015), bacteria-induced lysis (Rashidan and Bird, 2001), grazing by protists (Ger et al, 2014), algicidal compounds (Luo et al, 2013; and cyanobacterial programmed cell death (Franklin, 2014).…”
Section: Abioticmentioning
confidence: 99%
“…Inducible prophages have been found in several marine bacteria (Williamson et al, 2002;Mobberley et al, 2008) and are known to influence structure, biomass and genetic diversity of marine bacterial communities (Fuhrman, 1999). The genome of P. gallaeciensis DSM 17395 encodes an additional prophage-like element, which strongly resembles a so-called GTA (Supplementary Material S5), a virus-like particle that mediates transfer of genomic DNA between prokaryotes without negative effects on the host cell (Lang and Beatty, 2001).…”
Section: Geis Prophages and Gene-transfer Agents (Gtas)mentioning
confidence: 99%
“…However, the factors influencing the dynamics of viral abundance in aquatic environments might be dependent upon complex interactions of both abiotic factors such as pressure, redox conditions, temperature, light effects, and biotic like host abundance, host metabolic rate, viral supply (2,23,46).…”
Section: Introductionmentioning
confidence: 99%